Examining the Effect of 8-Week Educational Games on Gross Motor Skills in Children with Autism - Doğan, Hayriye; Aydem?r, İsa; Çinar, Vedat (Nevzat Demirci, 2024)
Families with autistic children expect their children to be self-sufficient and to play games like normal children. However, it appears that there are few initiatives and scientific research in our nation that would emphasize the importance of physical activity-based educational games in order to overcome this problem. The study's goal was to look at the impact of educational games on the development of gross muscular motor skills in people with autism. The study comprised 11 boys aged 10 to 12 who had never previously engaged in an educational game program on a regular basis. Measurements were gathered from the participants twice: once before the 8-week instructional gaming program and once after it ended. The control group received no instructional game software. The SPSS package application was used to perform statistical analysis on the data. There was a significant difference between the experimental group's pre-test and post-test results in hand grip, medicine ball throwing, speed, flexibility, sit-up, and balance (p<0.05). As a result, at the end of eight weeks, the educational game program based on physical activity and exercise had a positive influence on the gross motor abilities of children with autism. It may be recommended in this regard to further extend and promote educational game programs, as well as to include educational games in the education programs of children with autism. © 2024 Nevzat Demirci. All rights reserved.
Keywords: Autism; Educational Game; Motor Skills; Physical Development